Video Content Marketing as a Strategy to Increase Brand Awareness of PT Trusmi Group Properties on Social Commerce TikTok - Nadya Fatia Mahendra; Rezha Dwi Lestari; Misbak; Tiara MusThiarsih (Indonesian Journal of Business Analytics, 2025)
In the digita$l era$, socia$l media$ ma$rketing ha$s become importa$nt for increa$sing bra$nd a$wa$reness a$nd expa$nding a$udience rea$ch. TikTok ha$s emerged a$s a$ popula$r pla$tform a$mong the people, known for its crea$tive a$nd intera$ctive content. Levera$ged TikTok to increa$se its bra$nd a$wa$reness. The compa$ny enga$ges in crea$ting releva$nt content a$nd exploring innova$tive digita$l ma$rketing stra$tegies, especia$lly through TikTok's intera$ctive content a$nd promotiona$l fea$tures, to rea$ch a$ wider a$udience. This resea$rch a$ims to exa$mine the role of TikTok in increa$sing bra$nd a$wa$reness a$t PT Trusmi Group Housing which opera$tes in the Property sector. By a$na$lyzing the va$rious ma$rketing stra$tegies used on TikTok, a$nd their impa$ct on consumer perception a$nd memory, this resea$rch is expected to provide va$lua$ble insights for compa$nies in designing more effective digita$l ma$rketing ca$mpa$igns. In a$ddition, this resea$rch will a$lso explore the fa$ctors tha$t influence the success of ca$mpa$igns on TikTok, including content crea$tivity, intera$ction with users, a$nd the use of influencers.